Self-developed Controller System –based on Open-Source Applications - Erdei, Timotei; Molnár, Zsolt; Husi, Géza (International Journal of Engineering and Management Sciences, 2016)
In the University of Debrecen Building Mechatronics Research Centre faced by the application of building automation technology, are tackled by cutting edge research performed at the Research Centre. The embedded device system, the focus of the ongoing project at the Research Centre, is programmable, reconfigurable, and adjustable. The design of an efficient embedded system must meet regulatory requirements, for optimizing building energy efficiency. The system provides solutions for a range of industrial applications, and peaks the interest of building services providers (e.g. SMEs).